Effect of spinach powder on physico-chemical, rheological, nutritional and sensory characteristics of chapati premixes - Khan, M. A. (J Food Sci Technol, 2013)
Effect of spinach powder on the physico-chemical, rheological, nutritional and sensory characteristics on chapati premixes was studied by incorporating spinach powder at different concentrations from 1 % to 10 % based on wheat flour. Addition of 5 % of spinach powder to wheat flour was found to be optimum for chapati preparation. Effect of incorporation of spinach powder on the alveo-consistographic, mixographic and pasting characteristics were studied. It was observed that peak viscosity, breakdown viscosity significantly decreases whereas, peak time, tenacity increases with the increase in the concentration of spinach powder from 1 % to 10 % in chapati premixes. Addition of spinach powder also significantly affects the textural qualities of the chapaties. Premixes and prepared chapaties were also studied for chlorophyll content, total carotenoids,vitamins and minerals.